Structure and dft calculations of 2-{[3-methyl-3-phenyl-cyclobutyl)- thiazol-2-yl]-hydrazonomethyl}-phenol - Güntepe, F.; Saraçoglu, H.; Çaliskan, N.; Yüksektepe, Ç.; Çukurovali, A. (My University, 2011)
The title compound 2-{[3-Methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]- hydrazonomethyl}-phenol (C21H21N3S 1O1) crystallizes in the P-1 triclinic space group with a = 5.8880(4) Å, b = 9.5618(5) Å, c = 17.0484(10) Å, ? = 80.214(5)°, ? = 80.532(5)°, ? = 80.116(5)°. In addition to molecular geometry and packing from X-ray experiment, we have also calculated the molecular geometry and vibrational frequencies of the title compound in the ground state using density functional theory DFT (B3LYP) with the 6-31G(d,p) basis set. Apart from this, the structure of the title compound is characterized by 1H NMR, 13C NMR, IR and UV-vis. Spectra, and the experimental emission energies are compared with the HOMO-LUMO energy gaps calculated by the DFT method. Copyright © 2011 by F. Güntepe, H. Saraçoglu, N. Çaliskan, Ç. Yüksektepe, and A. Çukurovali.
Keywords: Crystal structure; DFT calculations; IR spectroscopy